HUBUNGAN PENGETAHUAN DENGAN PERILAKU DETEKSI DINI KANKER PAYUDARA MENGGUNAKAN TEKNIK SADARI PADA SISWI SMAN 1 PADALARANG TAHUN 2024 - nuraeni, rani; Triwidiyantari, Dyah; sri iriani, Oktarina (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2024)
The World Health Organization (WHO) states that in 2020 there will be 2.3 million women diagnosed with breast cancer and 685,000 deaths globally due to breast cancer. The incidence of cancer in Indonesia is still the highest for women, namely 42.1 per 100,000 population with an average death rate of 17 per 100,000 population. With this data in 2019, the cancer ranking in Indonesia ranks 8th in Southeast Asia and 23rd in Asia. This research aims to determine the relationship between knowledge and behavior in early detection of breast cancer using the BSE technique in female students at SMAN 1 Padalarang in 2024. This research uses an analytical survey method with a cross sectional approach. The total sample was 84 respondents using a proportional stratified random sampling technique. Data analysis used the chi square statistical test with α = (0.05). The results of this study show that there is a relationship between knowledge and early breast cancer detection behavior using the BSE technique in female students at SMAN 1 Padalarang in 2024 with a p value (0.000). Based on the research results, it can be concluded that there is a significant relationship between knowledge and early breast cancer detection behavior using the BSE technique in female students at SMAN 1 Padalarang in 2024.